2008
DOI: 10.1021/jf0731898
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Antifungal Activity of 10-Undecyn-1-ol by Inclusion Complexation with Cyclodextrin Derivatives

Abstract: The inclusion complexation behavior between 10-undecyn-1-ol and cyclodextrin (CD) derivatives, namely, randomly methylated beta-CD (RM-beta-CD) and hydroxypropyl-beta-CD (HP-beta-CD), was studied in terms of solubility improvement, apparent stability constant, and the inclusion ratios of the resultant inclusion complexes. The aqueous solubility of 10-undecyn-1-ol was greatly improved through complexation with the CD derivatives. RM-beta-CD is comparatively more efficient in solubilizing 10-undecyn-1-ol with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…SAS1 has previously been identified by GC‐MS as one of the phytochemical constituents of the plant Sarcostemma secamone (Kumari, Muthukumarasamy, & Mohan, ). This compound, which was also isolated in the leaf extracts of Azadirachta indica has limited solubility in water and has been determined to have antifungal activity (Neoh, Tanimoto, Ikefuji, Yoshii, & Furuta, ). Prior to this study, there has not been a report of the production of 10‐Undecyn‐1‐ol by a Penicillium species or by microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…SAS1 has previously been identified by GC‐MS as one of the phytochemical constituents of the plant Sarcostemma secamone (Kumari, Muthukumarasamy, & Mohan, ). This compound, which was also isolated in the leaf extracts of Azadirachta indica has limited solubility in water and has been determined to have antifungal activity (Neoh, Tanimoto, Ikefuji, Yoshii, & Furuta, ). Prior to this study, there has not been a report of the production of 10‐Undecyn‐1‐ol by a Penicillium species or by microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…1,8-Nonadiyne is reported to undergo one-step hydrosilylation reaction for attaching acetylene-terminated alkyl monolayers to nonoxidized crystalline silicon surfaces [17]. 10-Undecyn-1-ol has been reported to possess antifungal activity [18]. Some of these properties of the constituents detected in crude oil showed that it may be useful as or in production of certain antifungal.…”
Section: Discussionmentioning
confidence: 99%
“…Biological activities of some of the compounds identified in the avocado seed oil have been reported in literature. One of the major bioactive components of the oil, 10-Undecyn-1-ol, has been found to exhibit antifungal activity (Neoh et al, 2008). Devi and Serfoji (2018) have reported the antioxidant, hypocholesterolemic, antiandrogenic, hemolytic and alpha reductase inhibitory activities of 7-Hexadecenoic acid, methyl ester.…”
Section: Bioactive Compoundsmentioning
confidence: 99%